[Trends in rehabilitation of patients with rheumatic diseases in Germany] - Mau, W.; Beyer, W.; Ehlebracht-Konig, I.; Engel, J. M.; Genth, E.; Jackel, W. H.; Lange, U.; Thiele, K. (Z Rheumatol, 2014)
Recent Deutsche Gesellschaft fur Rheumatologie (DGRh, German Society of Rheumatology) guidelines emphasized the significance of coordinated multidisciplinary care and rehabilitation of patients with inflammatory rheumatic diseases. Nationwide data from the German pension insurance funds showed that inpatient rehabilitation due to rheumatoid arthritis (RA) varied by a factor of 2.6 between the different German states. From 2000 to 2012 rehabilitation measures were reduced by one third, most significantly in men with ankylosing spondylitis (AS). Rehabilitation measures because of RA or AS were provided up to 14 times more frequently by the German statutory pension insurance scheme compared with a large compulsory health insurance which is responsible for rehabilitation measures after retirement. In rehabilitation centers with high numbers of patients with inflammatory rheumatic diseases, higher structural and process quality were demonstrated. In 2011 a total of 40 % of RA patients in the national database of the collaborative arthritis centers showed medium or severe functional limitations. Among these disabled RA patients inpatient rehabilitation was reduced by about 50 % between 1995 and 2011. Out of all RA patients from outpatient rheumatology care with severe functional limitations 38 % had no functional restoration therapy within the previous 12 months with a high variation between rheumatologists. Experiences from other European countries may inspire German rheumatologists and other involved health professionals to initiate a wider range of rehabilitative interventions in the future.